Melittin Induces Local Order Changes in Artificial and Biological Membranes as Revealed by Spectral Analysis of Laurdan Fluorescence - Bogdan Zorilă; George Necula; Mihai Radu; Mihaela Bacalum (Toxins, 2020)
Antimicrobial peptides (AMPs) are a class of molecules widely used in applications on eukaryotic and prokaryotic cells. Independent of the peptide target, all of them need to first pass or interact with the plasma membrane of the cells. In order to have a better image of the peptide action mechanism with respect to the particular features of the membrane it is necessary to better understand the changes induced by AMPs in the membranes. Laurdan, a lipid membrane probe sensitive to polarity changes in the environment, is used in this study for assessing changes induced by melittin, a well-known peptide, both in model and natural lipid membranes. More importantly, we showed that generalized polarization (GP) values are not always efficient or sufficient to properly characterize the changes in the membrane. We proved that a better method to investigate these changes is to use the previously described log-normal deconvolution allowing us to infer other parameters: the difference between the relative areas of elementary peak (ΔSr), and the ratio of elementary peaks areas (Rs). Melittin induced a slight decrease in local membrane fluidity in homogeneous lipid membranes. The addition of cholesterol stabilizes the membrane more in the presence of melittin. An opposite response was observed in the case of heterogeneous lipid membranes in cells, the local order of lipids being diminished. RS proved to be the most sensitive parameter characterizing the local membrane order, allowing us to distinguish among the responses to melittin of both classes of membrane we investigated (liposomes and cellular membranes). Molecular simulation of the melittin pore in homogeneous lipid bilayer suggests that lipids are more closely packed in the proximity of the melittin pore (a smaller area per lipid), supporting the experimental observation.